PENGARUH STRUKTUR MODAL, LIKUIDITAS, PROFITABILITAS TERHADAP NILAI PERUSAHAAN PROPERTY DAN REAL ESTATE DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABLE MODERASI - indriana setya wardani; Achamad Tjahjono (Jurnal Akuntansi dan Bisnis, 2025)
The research focuses on evaluating the impact of capital structure, liquidity, and profitability on the value of companies engaged in the real estate sector and has been on the Indonesia Stock Exchange (IDX) list for the period 2018-2023. The more rapid and intense the competition faced by various companies in this field, the more this study seeks to determine the magnitude of the significant influence of all independent variables on the valuation of a company, as well as the role of company size, which is determined to be a moderating factor. Quantitative methods based on secondary data are the basis for conducting research, with the company's public financial statements as secondary data. Purposive sampling plays an important role as a form of sampling whose data is analyzed through multiple regression and moderation analysis. The findings of this study show that with positive significance, liquidity and profitability affect firm value, but capital structure does not exert its influence. In addition, firm size is found to moderate the interaction of liquidity with firm value but has no moderating effect on the relationship of capital structure and profitability on firm value..